A study of disaster preparedness of archives & museum in seismic zone - v, flood prone and conflict ridden Kashmir. (13th June 2020) - Najar, Jaffer Kabir; Wani, Zahid Ashraf
Abstract : Purpose: The purpose of this study is to develop a sense of urgency and utmost care for careful disaster management to encourage disaster preparedness for museums and archives.x In particular, this study examines the techniques and methods to be used for response and recovery from different disasters to save valuable resources. Design/methodology/approach: A thorough review of literature was done to identify existing plans, strategies, preparedness and management of archives and museums. On the basis of the knowledge and experience gained, it was decided to use a descriptive method for this study. Among the different data collection modes available in the descriptive method, the study framed a structured questionnaire for the collection of data. Thereafter, the questionnaire was tested for loopholes by conducting a pilot study. The questionnaire evolved as such was used to collect data from select archives and museums. The collected data has been tabulated and analyzed in tune with the set objectives. The findings of this study have been correlated with relevant findings and conclusions of previous studies in this domain to provide a better overview and sanctify the revelations further. Findings: From the current study, the authors find that the topological location of most of the institutions is near or on river banks which is the cause of concern at the time of heavy rains, after heavy snow fall and at the time of floods. It was also found that the majority of these institutions are located near highways which is also a serious concern in terms of noise, smoke, dust and vibrations produced by the plying of different types of transports on these highways. These kinds of unwanted disturbances create a negative atmosphere on the holdings, visitors and staff of these institutions.Although all of the institutions have apparently strong looking buildings that are made up of good material, the matter of concern is that only one institution (SPS museum) has a building which was specifically made for the purpose. As the state of Jammu and Kashmir is politically and geographically unstable, it is found that most of the institutions are prone to disasters like floods, earthquake and bomb threats which pose a threat to these valuable institutions and their valuable holdings.The most necessary and important parameter that is the training of the staff for disaster preparedness is not provided in majority of these institutions.Despite the fact that funds for majority of these institutions are provided by the government, the funds provided are insufficient for having fool-proof disaster preparedness and management. Research limitations/implications: Because of tremendous significance of archives and museums in propagation and preservation of historical and cultural identity of any nation, culture, ethnicity or nation state, the current study sheds light on the status of these important institutions in a very important part of Central Asia. Kashmir in past has been the cradle of knowledge evolution and sharing in the region. As such, it possesses some of the very rare manuscripts and artifacts preserved in her archives and museums. Practical implications: As this study is limited to select archives and museums of Jammu and Kashmir, the findings of this study may or may not represent the wider region of Central Asia.